2014
DOI: 10.1109/tmi.2014.2305691
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Lung Field Segmentation With Joint Shape and Appearance Sparse Learning

Abstract: Lung field segmentation in the posterior-anterior (PA) chest radiograph is important for pulmonary disease diagnosis and hemodialysis treatment. Due to high shape variation and boundary ambiguity, accurate lung field segmentation from chest radiograph is still a challenging task. To tackle these challenges, we propose a joint shape and appearance sparse learning method for robust and accurate lung field segmentation. The main contributions of this paper are: 1) a robust shape initialization method is designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

4
6

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 46 publications
0
51
0
Order By: Relevance
“…However, the classification is performed for each voxel independently, and also as noticed in our previous work (Wang et al, 2014a), the probability maps obtained by the random forest might introduce artificial anatomical errors in the final segmentation results. To deal with this possible limitation, we impose an anatomical constraint into the segmentation by using sparse representation, which has been employed in many applications (Gao et al, 2012; Shao et al, 2014; Wang et al, 2013b; Wang et al, 2014b). Specifically, by applying the trained classification forests, each training subject i can obtain its corresponding forest-based tissue probability maps (bold-italicIfalse‒bold-italici={IWMi,IGMi,ICSFi}).…”
Section: Methodsmentioning
confidence: 99%
“…However, the classification is performed for each voxel independently, and also as noticed in our previous work (Wang et al, 2014a), the probability maps obtained by the random forest might introduce artificial anatomical errors in the final segmentation results. To deal with this possible limitation, we impose an anatomical constraint into the segmentation by using sparse representation, which has been employed in many applications (Gao et al, 2012; Shao et al, 2014; Wang et al, 2013b; Wang et al, 2014b). Specifically, by applying the trained classification forests, each training subject i can obtain its corresponding forest-based tissue probability maps (bold-italicIfalse‒bold-italici={IWMi,IGMi,ICSFi}).…”
Section: Methodsmentioning
confidence: 99%
“…Many studies 37,38 have shown that learning multiple local models would help improve the prediction performance, compared to a single global model. Therefore, in this paper, we learn one regression forest for each brain tissue, i.e., WM, GM, and CSF.…”
Section: C1 Initial Prediction Of Standard-dose Pet By Multisourcmentioning
confidence: 99%
“…Previous attempts in the literature for the segmentation of lung field from CXR struggle to accommodate large anatomical and pathological variations found in pediatric CXRs. In addition, state-of-the-art existing methods, such as [8], [9], do not delineate parts of lung field behind aortic arch and apex of heart in CXR and therefore annotate the lung field only partially.…”
Section: Methodsmentioning
confidence: 99%